2011
DOI: 10.1146/annurev-pharmtox-010510-100611
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Anti-Cancer and Anti-Inflammatory Actions of Vitamin D

Abstract: Calcitriol, the hormonally active form of vitamin D, is being evaluated in clinical trials as an anti-cancer agent. Calcitriol exerts multiple anti-proliferative, pro-apoptotic, and pro-differentiating actions on various malignant cells and retards tumor growth in animal models of cancer. Calcitriol also exhibits several anti-inflammatory effects including suppression of prostaglandin (PG) action, inhibition of p38 stress kinase signaling, and the subsequent production of pro-inflammatory cytokines and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
349
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(360 citation statements)
references
References 191 publications
(221 reference statements)
5
349
0
6
Order By: Relevance
“…Recent research studies indicate that vitamin D 3 has antiinflammatory actions that likely contribute to its beneficial effects in multiple cancers (14,33). Inflammatory mediators, such as COX-2 and cytokines, enhance tumorigenesis through the activation of multiple signaling pathways in tumor tissue (17,37).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research studies indicate that vitamin D 3 has antiinflammatory actions that likely contribute to its beneficial effects in multiple cancers (14,33). Inflammatory mediators, such as COX-2 and cytokines, enhance tumorigenesis through the activation of multiple signaling pathways in tumor tissue (17,37).…”
Section: Discussionmentioning
confidence: 99%
“…S4B) confirmed the in vitro findings. The inhibition of p38 signaling is classically anti-inflammatory and has been hypothesized to contribute to some of the activities of vitamin D in cancer prevention (14). By protein analysis in vitro and in vivo, calcitriol treatment inhibits p38 phosphorylation in cells ( Fig.…”
Section: Effects Of Calcitriol On Il6 Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…1α 25(OH) 2 D 3 suppresses the expression of several genes which are involved in prostaglandin pathway. Several invitro and invivo studies on breast cancer and prostate cancer showed 1α 25(OH) 2 D 3 significantly decreases the expression of cyclooxygenase-2 (COX-2) and stimulates 15-PGDH levels (Krishnan & Feldman, 2011). However, several invivo studies showed the inverse correlation between VDR and both COX-2 and 15-Hydroxyprostaglandin Dehydrogenase (15-PGDH), as well as between PGE2 and 1α 25(OH) 2 D 3 levels suggests a possible link between VDR associated target genes and prostaglandin metabolism in breast cancer and ovarian cancer (Figure 3) (Thill et al, 2010a;2010b).…”
Section: Cyp24a1mentioning
confidence: 99%